Optimizing Volleyball Bottom Passing Skills: Unveiling the Impact of the STAD Learning Model on Learning Outcomes - Nurodin, Dede; ., Samsudin; Asmawi, Moch; Nurfitri, Wendah; Lubis, Johansyah; ., Junaidi; Humaid, Hidayat (KnE Social Sciences, 2024)
The study focused on improving the lower passing skills of 8th-grade female students at SMP Negeri 6 Sumedang in volleyball. Recognizing the significance of passing in enhancing team attacks and overall match performance, the researcher employed the student teams achievement division (STAD) learning model to address existing skill deficiencies. The research identified common issues in lower passing execution, including imperfect movement stages, improper ball contact in the hands, ball deviation from the intended target, and an inability to control the ball’s direction. The results indicated a positive impact, with a significant increase in the lower passing skills observed during the volleyball underpassing tests. The t-test results, with T_count = 16.4 > T_table = 1.725, demonstrated a statistically significant improvement, confirming that the STAD learning model contributed to enhanced learning outcomes. In summary, the research concluded that the application of the STAD learning model positively influenced the learning outcomes related to lower passing skills in volleyball among 8th-grade female students at SMP Negeri 6 Sumedang. The findings emphasized the efficacy of employing cooperative learning strategies, such as STAD, to address specific skill challenges in sports education. Keywords: STAD, bottom passing, volleyball